2023
DOI: 10.1111/jace.19106
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced optical transmittance and energy‐storage performance in NaNbO3‐modified Bi0.5Na0.5TiO3 ceramics

Abstract: Dielectric ceramics with both excellent energy storage and optical transmittance have attracted much attention in recent years. However, the transparent Pb-free energy-storage ceramics were rare reported. In this work, we prepared transparent relaxor ferroelectric ceramics (1 − x)Bi 0.5 Na 0.5 TiO 3 -xNaNbO 3 (BNT-xNN) by conventional solid-state reaction method. We find the NN-doping can enhance the polarization and breakdown strength of BNT by suppressing the grain growth and restrained the reduction of Ti 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The comprehensive energy-storage characteristic of 0.96 (0.7BNT-0.3ST)-0.04 SZN is superior to those of the reported BNT-based ceramics , with an excellent energy-storage performance at a low electric field of 290 kV/cm. Figure a shows that the W rec of 0.96 (0.7BNT-0.3ST)-0.04 SZN is higher than those of the reported lead-free energy-storage ceramics under similar electric fields (280–310 kV/cm). ,, The reported W rec values of lead-free ceramics can reach up to 7–8 J/cm 3 under an applied electric field strength of >400 kV/cm (Figure b). However, the W rec values of 0.96 (0.7BNT-0.3ST)-0.04 SZN reach 7.43 ± 0.05 J/cm 3 under an electric field strength of 290 kV/cm. Moreover, 0.96 (0.7BNT-0.3ST)-0.04 SZN has excellent temperature and frequency energy-storage stability and good charge–discharge properties ( P D ∼ 74 ± 1 MW/cm 3 and τ 0.9 ∼ 159 ± 2 ns) (Figures S2 and S4).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The comprehensive energy-storage characteristic of 0.96 (0.7BNT-0.3ST)-0.04 SZN is superior to those of the reported BNT-based ceramics , with an excellent energy-storage performance at a low electric field of 290 kV/cm. Figure a shows that the W rec of 0.96 (0.7BNT-0.3ST)-0.04 SZN is higher than those of the reported lead-free energy-storage ceramics under similar electric fields (280–310 kV/cm). ,, The reported W rec values of lead-free ceramics can reach up to 7–8 J/cm 3 under an applied electric field strength of >400 kV/cm (Figure b). However, the W rec values of 0.96 (0.7BNT-0.3ST)-0.04 SZN reach 7.43 ± 0.05 J/cm 3 under an electric field strength of 290 kV/cm. Moreover, 0.96 (0.7BNT-0.3ST)-0.04 SZN has excellent temperature and frequency energy-storage stability and good charge–discharge properties ( P D ∼ 74 ± 1 MW/cm 3 and τ 0.9 ∼ 159 ± 2 ns) (Figures S2 and S4).…”
Section: Resultsmentioning
confidence: 84%
“…(a) Comparison of W rec under similar electric fields strength (280–310 kV/cm) ,, and (b) electric field strength required for similar W rec (7–8 J/cm 3 ) values for 0.96 (0.7BNT-0.3ST)-0.04 SZN ceramic and reported lead-free energy-storage ceramics. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a comparison with recent reported work on lead-free ceramic energy storage properties is presented in Table 1. 8,23,27–37 Our work is very significant as it not only maintains higher W rec and η , but also has a leading W rec / E under a low electric field. (1 − x )BNT–BZT– x NN ceramics will shine in future energy storage components of power systems.…”
Section: Resultsmentioning
confidence: 91%
“…22 Similar features were also observed in other BNT-based ceramics modified with NaNbO 3 , CaZrO 3 , and NbTaO 3 . 23–25 It is noteworthy that the weak peaks ( T c ) appear in the high-temperature region [Fig. 4(b)–(d)], which is attributed to the contribution of the NN antiferroelectric phase.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the harmful effects of the Pb element, researchers are seeking lead-free materials to substitute lead-containing materials. , In the lead-free energy storage ceramics, BNT-based ceramics are considered to be one of the most promising substitutes for lead-based ceramics due to their large P max (>40 μC/cm 2 ) values . However, their high P r (≈38 μC/cm 2 ) leads to high W loss , which limits their application in energy storage. To improve its ESP, there are many effective ways, such as doping perovskite materials or oxides, adopting different sintering methods. For example, Zhou et al found a high W rec (3.52 J/cm 3 ) in 0.8Bi 0.5 Na 0.5 TiO 3 -0.2Sr­(Zr 0.2 Sn 0.2 Hf 0.2 Ti 0.2 Nb 0.2 )­O 3 ceramic. The dielectric constant of the sample has a wide range of temperature stability and a low value of dielectric loss.…”
Section: Introductionmentioning
confidence: 99%